What is the prenex normal form?

Overview

The prenex normal form is a method to deal with formulas so that the quantifiers are moved in front of the expression.

Prenex normal form

The prenex normal form is written as:

In this form QiQ_i is \forall or \exists where i=0,1,2...ni = 0, 1,2...n and FF is the quantifier-free formula. Q1x1 Q2x2...QnxnQ_1x_1 \ Q_2x_2...Q_nx_n is called the prefix, whereas FF is called the matrix.

A formula with no quantifiers is called a trivial case of the prenex normal form.

Steps to convert into PNF

We'll follow the steps below to convert any expression into PNF:

  1. We eliminate all the occurrences of \rightarrow and from the formula.
  2. We move all the negations inwards to appear only as a part of the literal.
  3. Standardize the variables apart if it is necessary.
  4. PNF is obtained by moving the quantifiers to the front of the formula.

Step 1

To remove the conditional \rightarrow (if AA then BB) and bi-conditional (AA if and only if BB), we use the following logical equivalences:

  • AB¬ABA \rightarrow B \equiv \neg A \vee B
  • AB(¬AB)(A¬B)A ↔ B \equiv (\neg A \vee B) \wedge (A \vee \neg B)
  • AB(AB)(¬A¬B)A ↔ B \equiv (A \wedge B) \vee (\neg A \wedge \neg B)

Step 2

We'll now try to move all the negations close to the literals instead of the negations occurring as a whole. We convert the \forall symbol to the \exists symbol and vice versa in this step when we shift the ¬\neg symbol. To accomplish step 2, we use the following logical equivalences:

  • ¬¬AA\neg \neg A \equiv A
  • ¬xA(x)x¬A(x)\neg \forall xA(x) \equiv \exists x \neg A(x)
  • ¬xA(x)x¬A(x)\neg \exists xA(x) \equiv \forall x \neg A(x)
  • De Morgan's law

Step 3

Renaming of the variables is called the standardizing of the variables apart. To achieve step 3, we use the following theorem to rename the variables to make them distinct.

Suppose we get AA' from AA by making some replacements in AA of the occurrences of Q(y)F(y)Q(y)F(y) by Q(x)F(x)Q(x)F(x). QQ can either be an existential or universal quantifier.

Step 4

In this step, we'll shift all the \forall and \exists to the beginning of the expression. To achieve step 4, we use the following basic logical equivalences:

  • AxF(x)x(AF(x))A \vee \forall xF(x) \equiv \forall x(A \vee F(x)) where xx does not occur in AA.
  • AxF(x)x(AF(x))A \vee \exists xF(x) \equiv \exists x(A \vee F(x)) where xx does not occur in AA.
  • AxF(x)x(AF(x))A \wedge \forall xF(x) \equiv \forall x(A \wedge F(x)) where xx does not occur in AA.
  • AxF(x)x(AF(x))A \wedge \exists xF(x) \equiv \exists x(A \wedge F(x)) where xx does not occur in AA.

Example

Let's consider the following expression:

To convert it into PNF, we follow the steps mentioned above.

Step 1

We'll eliminate \rightarrow and from the expression.

Step 2

We'll move the negations inwards.

Step 3

We'll standardize the variables.

Step 4

We'll now move the quantifiers to the front, and this gives us:

Output

In conclusion,

This is the final PNF form of the expression.

Free Resources

Copyright ©2025 Educative, Inc. All rights reserved